The Long‐Run Educational Cost of World War II - Ichino, Andrea; Winter‐Ebmer, Rudolf (Journal of Labor Economics, 2004)
An important component of the long‐run cost of a war is the loss of human capital suffered by school‐age children who receive less education. Austrian and German individuals who were 10 years old during the conflict, or were more directly involved through their parents, received less education than comparable individuals from nonwar countries, such as Switzerland and Sweden. We also show that these individuals experienced a sizable earnings loss some 40 years after the war, which can be attributed to the educational loss caused by the conflict. The implied consequences in terms of gross domestic product loss are calculated.